Evaluation of the Medical Image Compression using Wavelet Packet Transform and SPIHT Coding - Ismahane Benyahia; Mohammed Beladgham; Abdesselam Bassou (Institute of Advanced Engineering and Science, 2018)
Wavelet transforms and wavelet packets are widely imposed in the analysis and resolution of problems related to science and technical engineering. Decomposition wavelet packet allows several frequency bands according to various levels of resolutions. We apply this transform (PWT) coupled with the SPIHT coder to reduce the limitations of conventional wavelet filter bank. The results obtained using the applied algorithm, are very satisfactory and encouraging compared to many of the best coders cited in the literature and show a visual and numerical superiority over conventional methods. These the promising results are confirmed by visual evaluation parameters (PSNR, MSSIM and VIF).